2016
DOI: 10.2106/jbjs.16.00170
|View full text |Cite
|
Sign up to set email alerts
|

The Objective Measurement of Brace-Use Adherence in the Treatment of Idiopathic Clubfoot

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 32 publications
2
50
0
1
Order By: Relevance
“…However, as only 5 of the 12 measurements were taken with temperature sensors and the rest was based on questionnaires, the results are somewhat biased. A similar discrepancy between self-reported and objective measurement has also been observed in other fields of treatment, such as clubfoot and scoliosis therapy [17, 31].…”
Section: Discussionsupporting
confidence: 64%
“…However, as only 5 of the 12 measurements were taken with temperature sensors and the rest was based on questionnaires, the results are somewhat biased. A similar discrepancy between self-reported and objective measurement has also been observed in other fields of treatment, such as clubfoot and scoliosis therapy [17, 31].…”
Section: Discussionsupporting
confidence: 64%
“…Another consideration that may impact on long term conservative footwear management is compliance with the intervention [48]; this was not accounted for or was inconsistently measured in the studies potentially introducing confounding bias [49,50]. The medical conditions with the highest number of studies were pes planus (five studies) and cerebral palsy (four studies).…”
Section: Discussionmentioning
confidence: 99%
“…When using self-report, patients may find it difficult to accurately remember their adherence level, and studies on orthotic devices for other medical conditions have shown that self-report overestimates adherence. 46 , 47 However, using objective methods, such as temperature and activity monitors, is not without challenges.…”
Section: Methods To Measure Adherencementioning
confidence: 99%